2003
DOI: 10.1086/378095
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous Toll‐Like Receptor 4 Polymorphism Does Not Influence Lipopolysaccharide‐Induced Cytokine Release in Human Whole Blood

Abstract: The heterozygous Asp299Gly mutation of the toll-like receptor (TLR) 4, the key receptor for lipopolysaccharide (LPS), has been associated with attenuated inflammatory responses. When 160 healthy volunteers (9% heterozygous and 0.6% homozygous) were genotyped and their LPS-inducible cytokine release was assessed in an ex vivo whole blood test, the responses of heterozygotes did not differ significantly from those of wild-type carriers for any of the cytokines (tumor necrosis factor-alpha, interleukin [IL]-1beta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
42
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 33 publications
9
42
2
Order By: Relevance
“…38 However, several other groups report no significant evidence for a functional difference in ex vivo or in vitro characterization of cytokine expression by peripheral blood mononuclear cells between subjects having either the Asp or Gly allele at position 299. [39][40][41][42][43][44][45] It should be noted, however, that binding of the TLR4 receptor leads to more than just the activation of NFkB1. For example, signaling via TLR4 can also lead to the activation of the STAT family of proteins and the triggering of gene expression of the IRF family of proteins 46 -raising the possibility that TLR4 299Gly may affect the function of TLR4 signaling by another mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…38 However, several other groups report no significant evidence for a functional difference in ex vivo or in vitro characterization of cytokine expression by peripheral blood mononuclear cells between subjects having either the Asp or Gly allele at position 299. [39][40][41][42][43][44][45] It should be noted, however, that binding of the TLR4 receptor leads to more than just the activation of NFkB1. For example, signaling via TLR4 can also lead to the activation of the STAT family of proteins and the triggering of gene expression of the IRF family of proteins 46 -raising the possibility that TLR4 299Gly may affect the function of TLR4 signaling by another mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, other clinical and basic science investigations have failed to demonstrate a role for TLR4 in altering the inflammatory response. [19][20][21][22][23][24][25] There are several possibilities that may explain the lack of association between TLR4 genotype and measures of endotoxin signaling we have observed. [26][27][28] First, as there were no individuals homozygous for the TLR4 þ 896G allele, the remaining wild-type TLR4 allele in heterozygous carriers may be sufficient to elicit a normal response to endotoxin.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, reports that have demonstrated an association between endotoxin hypo-responsiveness and carriage of the TLR4 þ 896G allele have examined airway reactivity or systemic cytokine responses to inhaled endotoxin. [13][14][15] Studies that have not demonstrated an association were focused primarily on endotoxin responses in circulating leukocytes, 20,22,24,25 which mimics endotoxemia and clinical sepsis. 19,21 Numerous factors, including LBP, CD14 and serum HDL, among other molecules modulate LPS recognition and binding to TLR4, and interindividual differences in their effects may have important influences on leukocyte responses to endotoxin measured in our studies and seen clinically.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, an association of this TLR4 SNP with an increased risk of Gram negative infections and septic shock has been demonstrated (Agnese et al, 2002;Lorenz et al, 2002;Schrö der and Schumann, 2005). However, contrasting data have been obtained in other studies (Child et al, 2003;Erridge et al, 2003;Read et al, 2001;Heesen et al, 2003;Imahara et al, 2005;Schippers et al, 2005;von Aulock et al, 2003;Yang et al, 2004). Changes in eicosanoid levels are also correlated with SNPs in the promoter region of PTGS2 and 5-Lo genes, respectively codifying the cyclooxygenase-(Cox)-2 and 5-lipoxygenase (5-Lo), enzymes involved in arachidonic acid metabolism.…”
Section: Introductionmentioning
confidence: 95%
“…One or more functional SNPs in one or more genes might be responsible. Accordingly, recent studies have suggested the role of +896A/G TLR4 SNP in cytokine and eicosanoid production (Arbour et al, 2000;Ferwerda et al, 2007Ferwerda et al, , 2008Hoshino et al, 1999;Michel et al, 2003;Norata et al, 2005;Poltorak et al, 1998;von Aulock et al, 2003;Werner et al, 2003). On the other hand, an association of this TLR4 SNP with an increased risk of Gram negative infections and septic shock has been demonstrated (Agnese et al, 2002;Lorenz et al, 2002;Schrö der and Schumann, 2005).…”
Section: Introductionmentioning
confidence: 99%